RESEARCH OF READINESS FOR THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN MEDICAL EDUCATION - Inna I. Kucherenko; Pavlo V. Mykytenko; Tetiana S. Gruzieva; Anton H. Chebotarenko; Dmytro V. Zolotov; Kateryna О. Hololobova (Клінічна та профілактична медицина)
Introduction. Integration into the modern European educational environment brings a series of changes and modernization in approaches to the educational process, professional activities, and the need for digital solutions in everyday life. At the same time, the application and impact of artificial intelligence (AI) in the educational, scientific, and healthcare remain controversial.